PENGARUH PEMBERIAN JUS TOMAT DAN WORTEL TERHADAP PENURUNAN KADAR KOLESTROL PADA PASIEN HIPERKOLESTEROLEMIA - Vinorikanofia Vinorikanofia; Ratnaindahsaridewi Ratnaindahsaridewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Hypercholesterolemia is a condition in which serum cholesterol levels in the body have exceeded normal levels. Excessive cholesterol levels will settle down in the circulatory tract, thus narrowing the blood vessels and disrupting the normal circulatory system. One of the non-pharmacological therapies to help reduce cholesterol levels is the provision of tomato and carrot juice. Tomatoes and carrots are vegetables that contain many antioxidant compounds, including carotenoids, vitamin E, vitamin C and lycopene. Lycopene and carotenoids are antioxidants that are needed by the body. Aside from being an anti-aging, lycopene is also useful for preventing cardiovascular disease. In addition, tomatoes are also rich in fiber which is soluble in water and pectin content, especially in the skin, so it can interfere the absorption of fat and glucose from food. Carrots also contain pectin which is good for reducing cholesterol levels in the blood. The purpose of giving tomatoes and carrots juice is to minimize dependence on hypercholesterol patient in using pharmacological therapy. The research method is a quasi-experimental design with a sample of 24 respondents. The characteristics of respondents are 99% of women over 40 years. Randomly, the research subjects were divided into 4 groups, 3 treatment groups with different treatments (6 respondents were given tomato juice, 6 respondents were given carrot juice and 6 respondents with a combination of carrot and tomato juice) and one group as a control group, this research was done in 14 days. The results of this research are there are differences in the average cholesterol level in the respondents who consumed Tomato Juice, Carrot Juice, a combination of Tomato and Carrot Juice, and pharmacological drugs with the P value of 0.000